Does the game phase afect the design of tasks for a formative basketball team? - Mancha Triguero, D.; García Ceberino, J. M.; Antúnez Medina, A.; García Rubio, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
During the season, the main role of the coach is to design and plan the tasks that help achieve the objectives sequentially set. The aim of this study is to describe the existing differences between the tasks designed in function of the game phase. To do so, 388 tasks were collected during a season of a basketball team. This comparison is due to the fact that the coach performs the training under a comprehensive approach and chooses a wave model of work in which tasks are alternated with an aim of attack and defense. Finally, this study presents a critical and reliable analysis on the design and training plan with a global vision that shows the differences found in the tasks in function of the game phase.